Effect of Length of Soaking and Fermentation Using Palm Juice on Nutrient Content of Tamarind Seeds - Wea, Redempta; Balle-Therik, J.F.; Kalle, Pieter Rihi; Mulik, Marthen L. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Tamarind seed is an underutilized byproduct of tamarind fruit processing industry. It has rich nutrient contents but its utilization as feed is limited due to its association with a hard and non-destructive seed husk structure and the presence of anti-nutrient factors such as tannins and antitrypsin. Pre-treatment is needed to reduce or partially remove the anti-nutrients in order to increase its utilization. This study was conducted to determine the best treatment combination of soaking and fermentation using palm juice with tamarind seed which is yet unknown. Materials and Methods: Tamarind seeds were collected and sorted using a floating test. Selected seeds were then strained, dried and soaked in clean water. The study used a randomized complete design with a 3×3 factorial pattern and 3 replications. First factors was length of soaking (W0 = 0 days, W1 = 2 days and W2 = 4 days, second factor was level of palm juice (L0 = 0% of palm juice, L1 = 20% of palm juice and L2 = 40% of palm juice) and third factor was length of fermentation (F0 = 0 h, F1 = 36 h, F2 = 72 h and F3 = 108 h). Parameters measured were dry matter, crude protein, crude fat, crude fiber, Ash, Ca, P and tannin content. Results: The results showed that there was interaction between length of soaking, level of palm juice and length of fermentation. Soaking and fermentation using palm juice can improve the nutrients and reduce tannins of tamarind seed by 82.87%. Conclusion: The best nutritional value and lowest tannin content in tamarind seeds was achieved with 2 days of soaking and 20% palm juice at 72 h fermentation.